Some peculiarities of the associative holographic image formation and quality: the comparative analysis - Derzhypolskyy, A.; Melenevskyy, D.; Gnatovskiy, A.; Medved, N. (Functional Materials, 2005)
The peculiarities of associative holographic image formation at the initial image saving stage in different registration media have been studied. It is shown that the recovered associative holographic image quality can be theoretically predicted and is defined by the recovering beam area. The experiment and simulation results on the associative holographic image quality with the different reconstruction beam area are shown.